Factors Affecting NPAs of Scheduled Commercial Banks : An Empirical Study Based in Punjab - Uppal, R. K.; Khanna, Parul (Indian Journal of Finance, 2015)
The financial sector is always the key sector for the overall development of any country, and the banking sector is the primary sector amongst all. So, a strong banking sector is very important for the growth of the economy. This sector witnessed a lot of changes in our country after the 1991 economic reforms - popularly known as the era of "LPG," that is, liberalization, privatization,&globalization. The reforms focused on branch expansion, granting credit to the weaker sections like agriculture, SSI, education loans, housing, and so forth. However, in recent times, the banks have become very cautious in extending loans due to mounting non-performing assets (NPAs) and nowadays, managing NPAs is one of the major concerns for the banks as NPAs reflect the performance of the banks. A high level of NPAs suggests high probability of a large number of credit defaults that affect the profitability and net-worth of banks, and also erode the value of the asset. The NPA growth involves the necessity of provisions, which reduce the overall profits and shareholders’ value. The present paper explored the primary reasons for the growth of NPAs in scheduled commercial banks of Punjab and also suggested the measures for controlling the same.